Diagnóstico da qualidade da água e do sedimento do Rio Chopim no Refúgio de Vida Silvestre dos Campos de Palmas - PR - Schöninger, Francesca Cecilia Corso (2020)
The Conservation Unit Refuge Wildlifeof Campos de Palmas is extremely relevant for the conservation of a natural environment rich in biodiversity and remnants of natural southern fields interspersed with patches of mixed ombrophilous forest.However, adds to these environments agricultural areas, forestry, livestock and private properties which makes it vulnerable to contamination and degradation. However, adds to these environments areas of agricultural use and occupation, forestry, livestock and private properties which make it vulnerable to contamination and degradation. Based on this, the present study aimed to evaluate the water quality and sediment of the Chopim River through physical-chemical, microbiological parameters and with emphasis on determining the concentration of metals. The four stages of water and sediment sampling were carried out at five points along the Chopim River in the four seasons of the year. Statistical analysis and geochemical indexesassisted in the evaluation of the data trend and in the investigation of contamination of the sampling points. The physical and chemical results of the water compared to CONAMA Resolution 357/05 for Class II freshwater river, indicated that the Chopim River presented good levels of oxygenation, goodcapacity for self-purification and little stimulus to eutrophication detected low concentrations of the nutrients phosphorus and nitrogen. The highest concentrations of the studied metals werefound in the aquatic sediment. In water, the concentration of the elements Al, Cu and Fe showed values higher than those established in the legislation, and in the sediment, the concentrations of Pb, Cu and Zn were above the limits allowed by CONAMA Resolution 454/12, specific for sediment. The values of the parameters analyzed in the water samples of the Chopim River showed temporal variation, that is, by the season, while in the sediment,the tendency of the concentration of metals was the sampling points indicating spatial influence. Geochemical indexes of the sediment suggest contamination of the sediment with Pb and progressive pollution throughout the year.